An annotated type catalogue of amphibians and reptiles collected by Nikolay A. Zarudny in Iran and Middle Asia - Ananjeva, Natalia B.; Milto, Konstantin D.; Barabanov, Andrei V.; Golynsky, Evgeny A. (Zootaxa, 2020)
A complete catalogue is provided for the type specimens of amphibians and reptiles collected by Nikolay A. Zarudny and stored mostly in the herpetological collection of the Zoological Institute, Russian Academy of Sciences, St. Petersburg, Russia (ZISP), as of August 2018. The collection contains 270 type specimens, representing 51 taxa (species and/or subspecies) of one family of turtles, one amphisbaenia family, five lizard families and four snake families from 74 type localities. As a result of studying Zarudny’s collections, mainly from Iran, was the description by A. M. Nikolsky of two new genera, Microgecko and Diplometopon, and 42 species and subspecies (varieties). Twenty-two of these taxa are regarded currently as valid.